Studi In Vitro Aktivitas Antioksidan dan Antikolesterol Fraksi Etil Asetat Buah Pedada (Sonneratia casiolaris) - Nurhaija Arriyani; Danang Raharjo (Jurnal Kesehatan Amanah, 2026)
Pedada fruit (Sonneratia caseolaris) is a mangrove species recognized for its rich content of bioactive compounds that may provide various health benefits. This study aimed to evaluate the in vitro antioxidant and anticholesterol activities of the ethyl acetate fraction of pedada fruit and to analyze the correlation between these two biological activities. The extraction process was conducted using ethanol maceration followed by solvent–solvent fractionation to obtain the ethyl acetate fraction. Antioxidant activity was measured using the ABTS radical scavenging method, while anticholesterol activity was assessed through an in vitro cholesterol inhibition assay. The effectiveness of both activities was expressed in IC₅₀ values. The results demonstrated that the ethyl acetate fraction exhibited strong antioxidant and anticholesterol properties, with IC₅₀ values of 20.555 ppm and 9.636 ppm, respectively. Furthermore, Pearson correlation analysis showed a positive and statistically significant relationship between antioxidant and anticholesterol activities (r = 0.601; p = 0.005), indicating promising potential as a natural therapeutic agent.